Popularity of Indonesian Adolescents: Do the Findings from the USA Generalize to a Muslim Majority Developing Country?. Issue 2 (29th July 2015) - French, Doran C.; Niu, Li; Purwono, Urip
Abstract: This study investigated whether the pattern of behavior associated with popularity in the USA is also found in Indonesia. Participants were 452 7th (13 years) and 10th grade (16 years) Muslim students from West Java, Indonesia. Data were obtained from adolescents, peers, and teachers. Social preference and popularity were positively associated with prosocial behavior and number of mutual friends. Whereas social preference was positively associated with academic achievement and negatively associated with aggression, popularity was positively associated with aggression and tobacco use. These patterns of association are similar to those found in the United States. Indonesian society is highly hierarchical and popularity structures may build upon these stratifications.